Online News Consumption and Unfriending: A Mediating Moderated Role of Disagreement and Religiosity - Tayyeb Ramazan; Muhammad Shabbir Sarwar (Social Science Review Archives, 2025)
Social media platforms provide a space to discuss political matters, and at the same time, their features to filter and select exposure and friend lists lead to unfollowing and unfriending. Unfriending, unfollowing, and hiding are big problems in participatory democracy that create echo chambers on social media platforms. This study has attempted to explore the predictors of unfriending. Quantitative approach of survey methods has been applied to get the responses of 375 valid sample size through a nonprobability sampling technique of purposive sampling. It was found that online news consumption, online political discussion, and online political disagreement have significantly predicted unfriending. Similarly, multiple sequential mediations through the Hayes process were also applied, and it was found that political discussion and political disagreement mediate the relationship between online news consumption and unfriending. Moreover, it was also explored that religiosity did not have any impact as a moderator on the unfriending.